(untitled) (Urdimento: Revista de Estudos em Artes Cênicas, 2026)
This article is the result of postdoctoral research on the reemergence of lecture-performance language in the contemporary scene of the global South. In dialogue with recent studies by Brazilian and foreign researchers, a parallel was drawn between lecture-performance in the contemporary scene and the first experiences of lecture-performance in 1950. Furthermore, articulating the notions of “embodied researcher” (Messeder) and “oralitura” (Martins), an analysis of Grada Kilomba’s work Decolonizing Knowledge was carried out. The aim is to demonstrate that lecture-performance, in its resurgence in the global South, is a form that mobilizes the construction of embodied knowledge.